Achieving Physical Availability Target of Excavator PC210-10M0 Using FMEA and TNA at Sangatta - Stevanus Edwin Eka Aditiyanto; Maulahikmah Galinium; Dena Hendriana (Fakultas Teknik Universitas Islam Makassar, 2026)
ABC has received a complaint from PT. XYZ as their customer because of poor performance excavator PC210-10M0. The research problem is PC210-10M0 machines’ performance by Physical Availability (PA) of PT. ABC has been under target 85% for the last six months. Research objective is achieving target PA Excavator PC210-10M0 PT. ABC 85%. This research will follow the DMAIC framework with several analysis tools, including Fish Bone Diagram, Design Thinking, Training Need Analysis (TNA), and Failure Mode and Effect Analysis (FMEA) to find the most significant root cause of the problem. SWOT, TOWS, and QSPM analysis are used to find and select the most suitable strategies, then Cost-Benefit Analysis is used to determine the final action plan derives from the strategies. There are 5 action plans implemented: develop web-based applications, offer maintenance contracts, arrange basic maintenance training program, undercarriage replacement, and oil damper monitoring. After implementing the improvement activities, breakdown from undercarriage and engine reduce in duration and frequency. PA PC210-10M0 rise from 78.47% at the end of November 2024 to 88.56% at the end of July 2025. The implementation of Preventive Maintenance along with mechanics’ development programs, has a positive impact on the increase in PA of the PC210-10M0.